EFL STUDENTS’ CREATIVITY REFLECTED IN THE USE OF CATAPHORIC REFERENCES IN STUDENT CREATIVE WRITING - Ramadhani, Tria Rahayu; Iftanti, Erna (Universitas Gunadarma, 2024)
This study explores the impact of cataphoric references on coherence and creativity in non-native English speakers attending university-level creative writing courses. This research aims to address the question of whether students’ creativity is reflected through the use of cataphora in their writing. Using qualitative descriptive analysis, the author focuses on creative writing works from a Creative Writing Course at Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, employing purposive sampling from two students’ compilation books for diverse representation. Data collection involved systematically reading the compilation books, and noting instances of cataphoric and anaphoric references. The collected data were organized into tables, categorizing passages based on Longacre's text types. Analysis centers on cataphoric and anaphoric references, guided by Halliday and Matthiessen's theoretical framework (2014). This theoretical lens guided the exploration of the roles of cataphora in different text types and the subsequent understanding of its impact on students' creativity. The findings reveal that cataphora can function as both cohesive and creative tools, enhancing the creative dimension of a text by instilling suspense or a sense of anticipation. Interestingly, texts that abstain from using cataphora and solely utilize anaphora may enhance creativity through diction diversification. However, it is acknowledged that determining whether students’ creativity is reflected through the use of cataphora in their writing presents challenges. The study's limitations stem from the analysis of purposive samples, thus restricting the generalizability of the results. Despite limitations, this study significantly contributes to understanding the creative dimensions of cataphoric references in non-native English-speaking students' writing.